2021
DOI: 10.1101/2021.08.26.21262705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of SARS-CoV-2 vaccination in preventing severe illness and death – real-world data from a cohort of patients hospitalized with COVID-19

Abstract: Background: Due to the unprecedented speed of SARS-CoV-2 vaccine development, their efficacy trials and issuance of emergency use approvals and marketing authorizations, additional scientific questions remain that need to be answered regarding vaccine effectiveness, vaccination regimens and the need for booster doses. While long-term studies on the correlates of protection, vaccine effectiveness, and enhanced surveillance are awaited, studies on breakthrough infections help us understand the nature and course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
11
2
Order By: Relevance
“…Sagiraju HKR et al [12] from India conducted a similar study and reported a lower mortality rate in vaccinated patients; however, only 3% of patients in their study cohort were completely vaccinated as compared to 37.7% patients in our study. Almost 15% of the patients with breakthrough infections were asymptomatic, dyspnea was reported in 22%, and a higher proportion of unvaccinated patients were symptomatic in their study.…”
Section: Discussioncontrasting
confidence: 50%
“…Sagiraju HKR et al [12] from India conducted a similar study and reported a lower mortality rate in vaccinated patients; however, only 3% of patients in their study cohort were completely vaccinated as compared to 37.7% patients in our study. Almost 15% of the patients with breakthrough infections were asymptomatic, dyspnea was reported in 22%, and a higher proportion of unvaccinated patients were symptomatic in their study.…”
Section: Discussioncontrasting
confidence: 50%
“…However, a much lower effectiveness (22 to 29%) was estimated in a real-world setting during an analysis of cases in health care workers from April to May 2021 ( 117 ). All the same, monitoring of hospitalized COVID-19 patients between April and June 2021 indicated that the vaccines were highly effective in preventing severe illness ( 118 ).…”
Section: Inactivated Whole-virus Vaccinesmentioning
confidence: 99%
“…In a comparative study of vaccinated and unvaccinated individuals from our cohort, we found that vaccination significantly reduced the odds of developing hypoxia and death. [ 23 ] However, the presentation of silent hypoxia was not significantly different in the groups receiving the vaccination against COVID-19 and non-vaccinated groups. Further research on the pathogenesis of post-vaccination breakthrough infections is needed.…”
Section: Discussionmentioning
confidence: 99%